Towards a Conscious Integration of EDI Values on Canadian Campuses: A Case Study Analysis - Squires, Vicki; Gavu, Alexander; Moore, Hannah; Gopakumar, Rohan (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation, 2025)
Campuses are focusing on Equity, Diversity and Inclusion (EDI) initiatives and programs as a response to urgent calls for higher education institutions to exemplify these principles. This study focused on determining the current environment for embedding EDI principles to identify next steps in galvanizing efforts in this work. This qualitative multi-case study had two phases. In the first phase, we conducted an environmental scan of the websites of the 15 research-intensive universities in Canada (U15) to determine how EDI efforts were included in any publicly available documents and on the websites. In the second phase, we conducted semi-structured interviews with members of an EDI Champions committee at one campus to explore how the EDI commitments were being actualized on that campus. Participants confirmed that work was ongoing but that determining a shared understanding of EDI, articulating a strategy for implementation, and promoting EDI efforts on campus faced many challenges including creating understanding and commitment across campus to further the EDI strategies. Campuses need a well-articulated strategy complete with processes and targets to inform campus members about EDI, determine ways to support action, and articulate ways to measure progress against EDI goals.